SYMPTOM UPDATE BOARDS—DELIVERING EDUCATION AT THE FRONTLINE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Poultney, Jo; Maclaren, Sarah; Raper, Jude; Johnson, Helen; Tallon, Carole
Abstract : Background: Ensuring that we all deliver the best possible care requires continued learning and updating of our skills and knowledge. The challenge for all healthcare professionals is balancing the need to be on the frontline delivering care with the need for professional development. Myton Hospice recognised that an additional approach for education was needed to increase the opportunity for learning and so the symptom update boards were devised. Aim: One of the five commonest symptoms experienced by patients at the hospice was allocated to a senior clinician and they were asked to produce a board (24 inch by 32 inch) by using a variety of coloured marker pens to cover what they felt were the most important learning points about that symptom. All the information was based on the West Midland Palliative Care Physicians Guidelines to ensure we had consensus of opinion. A baseline assessment of knowledge was carried out. Each board was then placed in a prominent position at one of two inpatient units or three day hospices. The boards were accompanied by a question sheet to support their learning. Each board was kept in place for one month and then rotated round to a different unit. Results: The boards have been very well received by all of the nursing staff in the different units. The nurses have commented they are able to find some time during the working day to absorb some of the information given or they pick up facts even whilst carrying out their day to day work just by glancing at the board from time to time. Conclusion: Based on the enthusiasm for the boards we hope to continue developing this education tool further but await results of our assessment to determine if they have had a sustainable impact on knowledge around symptom management and if this translates into an improvement in patient care.